Socio-demographic profile and lung function status among tobacco wor - Haque, Md Ekramul; Nabi, Md Shah Golam; Debnath, Sumon Chandra; Noor, Irfan Nowroze; Monwar, Monalisa; Khan, Imran; Rahim, Zahidur; Rouf, Md Abdur (Asian Journal of Medical and Biological Research, 2017)
This cross-sectional study was conducted to assess the lung function status and socio-demographic profile of the tobacco workers. The study place was Akij Tobacco Industry which is situated in Sharsa Upazila under Jessore District of Bangladesh. The period of the study extending from January to December 2014. Tobacco worker who had worked in Akij Tobacco Industry, both male and female and working period more than one year. The total sample size was 203 and simple random sampling was done to select the workers on the basis of their identification number. Data were collected through face to face interviews using a semi-structured questionnaire and lung function status measured by the spirometer. About one-third (34.0%) of the workers was in the age group 40-60 years and mean age were35.8 ± 0.2 years. Of them the majority (54.1%) were male, 89.2% were married, and 48.3% were illiterate. More than half (53.2%) of the worker from the joint family and maximum (53.7%) respondents were in the income group 5000-10000 taka, 39.4% of the worker lived in katcha house and 95.5% were using the sanitary latrine. Approximately half (49.7%) of workers were working for more than 10 years and 66.5% of the workers were working daily for 6-8 hours. More than half (52.7%) of the workers were consuming tobacco product in which 62.3% used to smoke and 31.1% exposed to smokeless tobacco. The mean ± SD forced vital capacity in the 1st second (FEV1) was 2.25 ± 0.12 whereas forced vital capacity (FVC) was 2.59 ± 0.27 and the FEV1/FVC ratio was 87.16 ± 4.91.There was no significant (p>0.05) difference between male and female in their lung function status. There was a significant difference (p<0.05) was found between in mean score of FEV1/FVC ratio and the total working period. From the public health point of view, preventive measures need to be taken to control the dusty environment and wearing of personal protective masks. Asian J. Med. Biol. Res. June 2017, 3(2): 205-210